Macias Vera,Diego Rafael(2023)ESTABLECIMIENTO DE UN JARDÍN CLONAL PARA LA CONSERVACIÓN DE CLONES DE CACAO (Theobroma cacao L.) TIPO NACIONAL.Quevedo.UTEQ.61p. - Macias Vera , Diego Rafael (2023)
The research was carried out on the ¨La María¨ University campus belonging to the Quevedo State Technical University, located at Km 7 of the Quevedo road, the junction, Mocache Canton, province of Los Ríos. Establishment of a clonal garden for the conservation of clones of cacao (Theobroma cacao L.) National type was carried out. For this reason, a completely randomized block design was used with 10 repetitions in a distance of 3 m x 3 m in a plot made up of 9 plants per repetition, and the following variables were recorded: number of healthy ears, number of diseased ears, weight fresh, yield, number of dead grafts, percentage of seizure, percentage of mortality in nursery, number of leaves, plant height. Regarding the ear number, the clones L12H27 and L12H8 stood out with 282.88 and 205.00 respectively. Regarding the number of diseased ears, the clones L12H27 and L17H30, registered a higher degree of tolerance. The highest fresh weight was recorded in clones L12H27 and L12H8 with 23.79(Kg) and 17.41(Kg). And in yield I indicate the clones L18H59 and L12H27 with 5428.38 and 5733.20 and in their order. The clone L12H29 and L12H presented a higher ear index with 67.75 and 66.19. the clone that presented the highest seed index was L45H11 and L17H30 with 1.70 and 1.42. The clone L12H29, EET801 and L17H30 presented the highest number of grafts on with 9.67, 9.67 and 9.33. the clone L20H48 and L45H11 gave the highest percentage of mortality with 16.67 and 10.00. the clone EET801 Y L12H29 that reached the highest percentage of take with 96.67 and 96.67. the clones that were higher in avocado height are L45H11 and L12H8 with 36.96 and 35.85 cm. Clones L46H75 and L45H11 presented a greater number of leaves with 20.90 and 16.80.